Numerical simulation of damage accumulation and fatigue crack growth in elastic materials - Korolev, Igor Konstantinovich; Petinov, Sergey Vladimirovich; Freidin, Alexander Borisovich (Computational Continuum Mechanics, 2009)
A FEM-based procedure for simulation of fatigue crack growth in the field of progressive damage is developed. A new finite element grid is suggested in this procedure to consider damage accumulation and fatigue crack growth based on a unified point approach. The grid design allows saving information on accumulated damage and «natural» tracing of a growing crack, which is a laborious task in the case of standard FEM-procedures. With application of the proposed grid, the fatigue behavior of a thin rectangular plate with randomly distributed initial defects under cyclic loading conditions is analyzed. Defects in the material structure are modeled by the elements with negligibly small stiffness. Fatigue properties are described by the Basquin equation. The trajectories of growing cracks and damage accumulation in the plate are presented for different phases of fatigue life.
Keywords: damage accumulation; fatigue crack growth; FEM simulation; crack path; mesh type